Durability Evaluation of Normal and High Performance Concrete (Global Journals of Research in Engineering, 2022)
Classification of concrete is often most feasible means for measuring the durability and has become progressively over the past 20 years. The present study is focused on the capability of concrete to improve its durability when the concrete is subjected to the highly aggressive environments. Existing concrete in cold or coastal regions are affected by chloride penetration under the freeze-thaw cycles. This collective deterioration process quickens the damage advancement of concrete and reduces the service life of the structures. In real life the structure may face numerous deterioration contrivances due to environmental factors surrounded by the concrete. A variety of laboratory test method were used for the determination of durability, which provide number of results, such as rapid chloride penetration value, electrical conductivity, water absorption rate in concrete. For evaluating the durability of concrete, to a single contrivance of deterioration, the techniques were economical and appropriate. For determining the durability of concrete the Ordinary Portland Cement was used. Two different concrete were tested: one the M30 grade of concrete and one M60 grade of concrete, to show the influence of water/cement ratio on durability of concrete. A total of 12 specimens were prepared and were tested for the compressive strength after 7, 14, and 28 days. Based on the results, it was observed that there was a drop of strength after the specimens were put exposed to solution curing.
Keywords: ordinary portland cement; high performance concrete; electrical conductivity; compressive strength